Synthesis, characterization and dielectric properties of novel axial coumarin-substituted titanium(IV) phthalocyanines - Altun, Selcuk; Altindal, Ahmet; Bulut, Mustafa (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The oxotitanium(IV) phthalocyanine (2) and axial coumarin-substituted derivatives (5 and 6) have been synthesized, and characterized by IR, UV-Vis, fluorescence, H-1 NMR, MALDI-TOF mass spectrometry and elemental analysis. It was observed that the reaction of novel oxotitanium(IV) phthalocyanine with orthodihyroxycoumarin compounds gives its derivatives, substituted by coumarin at the axial position. The electronic and interface state density properties of the Ag/Pc/p-Si diodes have been investigated by current-voltage (I-V) and conductance-frequency-voltage (G-omega-V) methods. It was found that, the conduction mechanism of the diodes is controlled by the thermoionic emission mechanism. From the analysis of frequency, omega, dependence of electrical conductivity, sigma(ac), it was found that the sigma(ac) obeys the power law given by sigma(ac), = sigma(0)w(s). The interface state density of the diodes were determined from (G/omega)-omega plots. It was found that the kind of substitution affects both the interface and omega electrical properties of the phthalocyanine complexes considerably. The obtained results show that the Ag/6/p-Si heterojunction is a good candidate for the electronic device applications. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Titanium phthalocyanine; Coumarin; Dielectric; Metal-insulator-semiconductor structure; Impedance; Interface state density; Fluorescence; ELECTRICAL-CONDUCTIVITY; ACTIVE MATERIALS; AC CONDUCTIVITY; TEMPERATURE; FREQUENCY; PHOTOCONDUCTIVITY; CHALCOGENIDE; REACTIVITY; MECHANISM; VOLTAGE; Chemistry; Crystallography